Studying the Development of Education Infrastructure’s Spatial Plan at Kendari - Malesa Malesa (International Journal Labs, 2021)
The study aims to: 1) analyze accessibility and mobility factors the planned development of educational facilities in Kendari City; 2) analyze strategy for planning the development of educational facilities for the next 10 years in Kendari City. The type of study is descriptive qualitative and quantitative research, carried out in all high schools and vocational schools in Kendari City totaling 30 schools spread over 10 sub-districts. The results show that: i). The closest distance to reach educational facilities is 579.091 meters, while the farthest is 175.236.993 meters; ii). The highest accessibility value classifications are 13,11 and 10, moderate classification 8, 7, and 6, while the lowest classification is 5, 4, and 3; iii). The priority for improving educational facilities in the next 10 years, namely in 2021 requires 44 units; in 2022 46 units; in 2023 47 units; in 2024 48 units; in 2025 49 units; in 2026 50 units; in 2027 52 units; in 2028 53 units; and in 2029 54 units. The closest distance to reach educational facilities is SMA Negeri 4 Kendari using 2-wheeled vehicles from the city center, while the farthest distance is SMA Negeri 8 Kendari. The classification of the highest level of accessibility is Baruga District, Wua-Wua, West Kendari. Meanwhile, Puwatu, Kadia, Kambu and Abeli ??Districts are classified as the lowest. The priority areas for improving vocational education facilities for the next 10 years are in Kambu District 1 unit, Baruga 1 unit, Puwatu 1 unit and Poasia 1 unit. While the high school level is Mandonga District 1 unit, Poasia 1 unit, Kambu 1 unit, Puwatu 1 unit. The Districts of Wua-Wua, West Kendari and Kadia do not require additional educational facilities until 2029.